Monsters of film, fiction, and fable : the cultural links between the human and inhuman - Bro, Lisa Wenger; O'Leary-Davidson, Crystal; Gareis, Mary Ann (Cambridge Scholars Publishing, 2018)
Monsters are a part of every society, and ours is no exception. They are deeply embedded in our history, our mythos, and our culture. However, treating them as simply a facet of children's stories or escapist entertainment belittles their importance. When examined closely, we see that monsters have always represented the things we fear: that which is different, which we can't understand, which is dangerous, which is Other. But in many ways, monsters also represent our growing awareness of ourselves and our changing place in a continually shrinking world. Contemporary portrayals of the monstrou.